Recombinant sclerostin antagonizes effects of ex vivo mechanical loading in trabecular bone and increases osteocyte lacunar size - Kogawa, M; Khalid, Kamarul Ariffin; Wijenayaka, Asiri R; Ormsby, Renee T; Evdokiou, A; Anderson, Peter H; Findlay, David M; Atkins, Gerald J (2018)
Sclerostin has emerged as an important regulator of bone mass. We have shown that sclerostin can act by targeting late osteoblasts/osteocytes to inhibit bone mineralization and to upregulate osteocyte expression of catabolic factors, resulting in osteocytic osteolysis. Here we sought to examine the effect of exogenous sclerostin on osteocytes in trabecular bone mechanically loaded ex vivo. Bovine trabecular bone cores, with bone marrow removed, were inserted into individual chambers and subjected to daily episodes of dynamic loading. Cores were perfused with either osteogenic media alone or media containing human recombinant sclerostin (rhSCL) (50 ng/ml). Loaded control bone increased in apparent stiffness over time compared with unloaded bone, and this was abrogated in the presence of rhSCL. Loaded bone showed an increase in calcein uptake as a surrogate of mineral accretion, compared with unloaded bone, in which this was substantially inhibited by rhSCL treatment. Sclerostin treatment induced a significant increase in the ionized calcium concentration in the perfusate and the release of -CTX at several time points, an increased mean osteocyte lacunar size, indicative of osteocytic osteolysis, and the expression of catabolism-related genes. Human primary osteocyte-like cultures treated with rhSCL also released -CTX from their matrix. These results suggest that osteocytes contribute directly to bone mineral accretion, and to the mechanical properties of bone. Moreover, it appears that sclerostin, acting on osteocytes, can negate this effect by modulating the dimensions of the lacunocanalicular porosity and the composition of the periosteocyte matrix.